The implementation of English and Arabic practices at an Islamic bilingual boarding school - Silviyanti, Tgk Maya; Yusuf, Yunisrina Qismullah; Samad, Iskandar Abdul; Mukminin, Amirul (LPMPP Universitas Negeri Yogyakarta, 2024)
The study aims to identify challenges teachers and students face in this process at an Islamic bilingual middle boarding school in Aceh, Indonesia. The participants included 27 boarding school students, one English teacher, and one Arabic teacher. The collected data underwent analysis using the interactive analysis model, which involves data reduction, display, and verification. The analysis focuses on specific activities within five categories: (1) mufradat (vocabulary), (2) controlling language use, (3) muhadasah (conversational activities), (4) competition, and (5) cooperation. The findings revealed that not all specified activities were consistently carried out, with each category featuring three implemented activities: daily vocabulary memorization, language festivals, and the application of punishments. The interviews brought forth challenges such as teachers' language proficiency limitations, students' low motivation, and a tendency to use the Indonesian language when unsupervised. These insights provide valuable guidance for similar boarding institutions that implement comparable language programs.